Increased Serum Neurotrophin Levels Related to Alcohol Use Disorder in a Young Population Sample. (January 2015) - Lhullier, Alfredo C.; Moreira, Fernanda P.; da Silva, Ricardo A.; Marques, Melina B.; Bittencourt, Guilherme; Pinheiro, Ricardo T.; Souza, Luciano D. M.; Portela, Luis Valmor; Lara, Diogo R.; Jansen, Karen; Wiener, Carolina D.; Oses, Jean Pierre
<x xml:space="preserve">Abstract</x> Background The diagnosis of alcohol use disorder is based on clinical signs and on the measurement of biological markers. However, these markers are neither sufficiently sensitive, nor specific enough, for determining the effects of alcohol abuse on the central nervous system. Serum neurotrophins are important regulators of neural survival, development, function, and plasticity and have been found to be reduced in alcohol use disorder. The aim of this study was to investigate the alterations in serum neurotrophin levels (brain‐derived neurotrophic factor [BDNF], glial‐derived neurotrophic factor [GDNF], and nerve growth factor [NGF]) in alcohol use disorder in a young population, and thus possibly representing the early stages of the illness. Methods This is a cross‐sectional study, nested in a population‐based study of people aged 18 to 35, involving 795 participants. The participants responded to the CAGE questionnaire, and a CAGE score of ≥2 was considered to be a positive screen for the abuse/dependence or moderate to severe alcohol use disorder. Serum BDNF, GDNF, and NGF levels were measured by ELISA. Results In the CAGE ≥ 2 group, GDNF (p ≤ 0.001) and NGF (p ≤ 0.001) serum levels were significantly increased, and the BDNF elevation was near a statistical significance (p = 0.068) when compared to the CAGE < 2 group. A significantly positive correlation was observed only in the CAGE ≥ 2 group for BDNF/GDNF (r = 0.37, p < 0.001) and GDNF/NGF (r = 0.84, p < 0.001) levels. The correlation between the NGF and BDNF levels was significantly positive in both groups (r = 0.28, p < 0.001 for the CAGE < 2 group, and r = 0.30, p = 0.008 for the CAGE ≥ 2 group). Conclusions These results suggest that elevated neurotrophins are candidate markers for the early stages of alcohol misuse.